Integrating crafts in a CLIL approach for enhancing vocabulary acquisition and subject comprehension among fifth-grade students (2024)
ABSTRACT: This study inquires into how integrating crafts within a Content and Language Integrated Learning (CLIL) approach enhances both language acquisition and content comprehension among 46 fifth-grade students at Juan María Céspedes School in Medellín, Colombia. As a public institution located in a city marked by social and economic contrasts, the school plays a crucial role in providing not only education but also a safe space for personal growth and community building. Although the school promotes bilingualism and follows a curriculum aligned with international standards, challenges persist, including limited teacher proficiency in English and a lack of structured resources for effective CLIL implementation.Through classroom observations, student assessments, and discussions with the cooperating teacher (CT), this research explores how craft-based activities within CLIL lessons can address these challenges by fostering both academic performance and student engagement. Early observations reveal that students respond positively to craft-integrated lessons, showing increased enthusiasm, participation, and motivation to engage with both language and content. Teacher feedback further highlights the practicality of this approach in large classroom settings, offering a creative and interactive alternative to traditional methods.This study aims to provide practical insights for primary school teachers struggling with English instruction by demonstrating how crafts can enhance student outcomes in a bilingual context. The findings could possibly contribute to the development of effective CLIL practices at the school, aligning with their goal to integrate language learning across all subjects and meet international standards by 2025. Ultimately, this research offers a framework for promoting meaningful learning experiences through creative methods, benefiting both students and educators in public primary classrooms.